Functional Disruption of the Constitutional Monarchy and the Transition to Enlightened Tyranny: A Functionalist Analysis of the Change in the Governance Method - aboalghasem shahryari; Seyed Hosein Athari; Mohsen Khalili; Mahdi Najafzadeh (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2023)
Statement of the ProblemThe March 1921 coup and the rise of Reza Khan, under the so-called enlightened tyranny referred to by Iranian thinkers, ended more than a century-long reign of the Qajar dynasty. Although the Qajar monarchy was transferred to the Pahlavi in 1925, the rule in Iran was practically out of the control of the Qajars since March 1921. Having risen to power with the coronation of Agha Mohammad Khan in 1796, the Qajars inherited a situation resulted from about a century-long conflict and chaos in Iran, for the rule had changed five times in less than seventy-five years: the fall of the Safavid dynasty, the rise of Afghans to power, the Afsharid dynasty, the Zand dynasty, and finally the Qajar dynasty. The perpetual riots and insecurities led to the migration of a large number of Iranian thinkers and even religious scholars to India and the Ottoman lands. Concomitant with the chaos in eighteenth-century Iran, the entire world experienced remarkable developments in inventions, discoveries, and the governance method, which went totally unnoticed by Iran and Iranians. However, the relative stability during the Qajar dynasty resuscitated political thought focused on preparing the ground for continuity and durability of the state and achieving the progress in light of the putative security, for the Iranian thinkers of the first generation (e.g., Shoushtari, Esfahani, and Kermanshahi) referred to the change in the governance method and the ensuing peace and security as the reason for progress of other countries.MethodologyThe present study uses the method of qualitative content analysis to analyze the treatises and travelogues of the Qajar era. Reading and categorizing the material presented by Iranian and non-Iranian thinkers in the Qajar era, the research relies on the theory of structural functionalism to investigate the cause underlying the transition to enlightened tyranny. The study is based on the hypothesis that the functional disruption of the social system of Qajar Iran and the ensuing inefficiency in the governance method of the Constitutional Movement had the Iranian thinkers think of a new order for the governance in Iran.FindingsA) From absolute monarchy to constitutional monarchy: Conceptual development and stability of governanceFor the Iranian thinkers, the specific method of governance in Iran was the main cause of the chaotic situation manifested in the continuous change of governments, governors, or  ministers, so the thinkers attended to the restoration and reform of the governance system. However, the outbreak of the Russo-Persian wars rendered Fath Ali Shah’s initial efforts ineffective, and subsequent, unremitting internal riots totally distracted his attention from the matter.During the early reign of Naser al-Din Shah and Amir Kabir’s tenure as the chief minister, an attempt was made to improve Iran’s social system and eliminate anarchy, which could bring about some changes in the short run. However, the assassination of Amir Kabir, the Treaty of Paris, and the subsequent separation of Herat once again drew attention to the governance method. Throughout the reign of Naser al-Din Shah and Mozaffar al-Din Shah, the Iranian thinkers would emphasize the need to change the governance method in order to improve the living conditions of Iranians and organize Iran’s social system.Despite some efforts, the overall circumstances did not improve from the beginning of the Qajar dynasty to the end of the Mozaffari era. Although the anarchy deepened, the attempts at reforms transformed the concept of moderate monarchy into constitutional monarchy, which fruitfully led to establishing the National Council and writing the law at the end of the Mozaffari era. The objective to introduce a solution to the functional disruption under the limited power was essentially accomplished, leading to a new method of governance in Iran.B) Persistence of functional disruption in constitutional governanceThe reports about Iran during the constitutional era prove that the panacea for Iran’s problems was not the establishment of the parliament or control of the government but the creation of a structure to implement decrees, for the constitutionalism would also lead to a new dictatorship in the absence of administrative and judicial mechanisms. From the mid-1910s, the circumstances stressed the need for an organized judicial system and a single and integrated administrative apparatus to resolve the functional disruptions, especially in economic and political sectors. The need existed because the constitutional monarchy had turned into the tyranny of constitutionalists, without reforming the functional anarchy.ConclusionApplying the theory of structural functionalism to analyze Iran’s situation at the end of the nineteenth century makes it clear that enlightened tyranny was an attempt to end the functional disruption in the four dimensions of Iran’s social system. Resulted from the constant chaos and conflict in eighteenth-century Iran, the functional disruption lasted well through the century-long reign of the Qajars, and the efforts to fix or reform each of the four dimensions failed in bringing about a noticeable and positive effect on the life of Iranians.Maintaining or creating order in a social system requires the functional adaptation of all dimensions of the social system. In this regard, the adaptation of the two subsystems of economy (with the function of provision of goods and services) and politics (with the function of allocation and decision-making) is absolutely necessary. The study of Iran during the period of the constitutional monarchy shows that the subsystemic adaption did not exist between economy and politics, so the functional disruption in the economic subsystem made the subsystem of politics conclude the Anglo–Iranian agreement of 1919 with the purpose of financing. This makes clear the very disruption in the most fundamental functioning of the system of Qajar Iran, which, following the functional logic, effected the non-adaptation and dysfunctionality of other dimensions as well.The persistence of the situation even within the constitutional governance ultimately underscored the need for something more than legislation, leading to a conceptual change of the limit of power and adoption of Japanese and German models of establishing a centralized and powerful structure to effect the reforms demanded by the thinkers. This played the role of what is known in structural functionalism as the external environment, and the coup of 1921 took place and helped enlightened tyranny take over the governance in order to fix the functional disruptions of the social system and establish a new order in Iran.